Emerging roles of xenobiotic detoxification enzymes in metabolic diseases - Petriello, Michael C (Rev Environ Health, 2017)
Mammalian systems have developed extensive molecular mechanisms to protect against the toxicity of many exogenous xenobiotic compounds. Interestingly, many detoxification enzymes including cytochrome P450s and flavin-containing monooxygenases, and their associated transcriptional activators (e.g., the Aryl hydrocarbon receptor), have now been shown to have endogenous roles in normal physiology and the pathology of metabolic diseases. This mini-review will focus on two such instances; the role of flavin-containing monooxygenase 3 (FMO3) in the formation of the cardio-metabolic disease biomarker trimethylamine-N-oxide (TMAO), and the role of AhR as a sensor of endogenous ligands such as those generated by the gut microbiota. Understanding the roles of xenobiotic sensing pathways in endogenous metabolism will undoubtedly lead to a better understanding of how exposure to environmental pollutants can perturb these physiological processes.